Perovskite band engineering for high-performance X-ray detection - He, Yichu; Wang, Zeshu; Wang, Zi; Dun, Guan-Hua; Geng, Xiangshun; Wang, Chunlin; Du, Jingbo; Guo, Tianyu; Xie, Dan; Tian, He; Yang, Yi; Ren, Tian-Ling (Frontiers in Physics, 2023)
Perovskite-based X-ray detector, which is widely applied in fields of scientific research and medical diagnosis, has drawn much attention for its superior optoelectrical properties. To improve the detection performance, band engineering is becoming the hot topic for perovskite properties modulation. In this article, we review the recent progress of perovskite-based X-ray detectors with band engineering process from four aspects, which are background introduction, band theory, heterojunction devices, and optimized electrode contact devices. Lastly, research status and strategies are summarized and perspectives of future progress are analyzed. We hope this review can provide constructive instructions and suggestions for future development of band engineering for perovskite-based high-performance X-ray detector.